Association between glutathione peroxidase‐3 activity and carotid atherosclerosis in patients with type 2 diabetes mellitus - Ping Ling; Wanying Shan; Guojie Zhai; Chunfang Qiu; Yuan Liu; Yuan Xu; Xiuyan Yang (Brain and Behavior, 2020)
Abstract Background and Aims Deficiency of glutathione peroxidase 3 (GPx3) has been recognized as an independent risk factor for cardiovascular events. However, little is known regarding the role of GPx3 in carotid atherosclerosis, which is ubiquitously observed in type 2 diabetes mellitus (T2DM). This study aimed to investigate the relationship between GPx3 activity and carotid atherosclerosis among patients with T2DM. Methods From January 2018 to December 2018, 245 consecutive patients with T2DM were enrolled in this observational study. Assessment of serum GPx3 activity was performed after admission. We also used carotid ultrasound to measure the mean carotid intima–media thickness (CIMT) and to assess the presence of carotid plaque. Results Of the 245 patients, the median serum GPx3 activity was 22.5 U/ml (interquartile range, 12.4–35.9 U/ml). Carotid plaque was observed in 113 (46.1%) patients, and mean CIMT was 0.8 ± 0.1 mm. Univariate analysis showed that age, smoking, previous coronary heart disease, carotid plaque, and level of mean CIMT and hypersensitive C‐reactive protein were significantly associated with decreasing tertile of GPx3. Furthermore, after adjusting for all potential confounders by multivariable logistic regression analysis, PGx3 activity was significantly and independently associated with the mean CIMT (β = −.406, p = .002) and carotid plaque (first tertile of GPx3, odds ratio, 1.870, 95% confidence intervals, 1.124–3.669, p = .024). Conclusions This study demonstrated that serum GPx3 activity was inversely associated with mean CIMT and carotid plaque, suggesting that lower GPx3 activity may be an independent predictor for carotid atherosclerosis in T2DM.